PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TRIDAYA DIMENSI INDONESIA DI JAKARTA SELATAN - Aila Putri Alfisiana; Safiih, Abdul Rahman (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and work motivation on employee performance at PT Tridaya Dimensi Indonesia in South Jakarta. This research used a quantitative method with a sampling technique using saturated sampling and obtained a sample of 58 respondents. The analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of the calculated t hypothesis test of 3.845 > t table 2.003 with a probability value (sig) of 0.000 < 0.05, it can be concluded that partially work discipline has a positive and significant influence on employee performance at PT Tridaya Dimensi Indonesia in South Jakarta. Based on the results of the hypothesis test t count 6.123 > t table 2.003 with a probability value of 0.000 < 0.05, it can be concluded that partially work motivation has a positive and significant influence on employee performance at PT Tridaya Dimensi Indonesia in South Jakarta. Based on the results of hypothesis testing with a calculated f value of 84.898 > f table 3.19 with a probability value (sig) of 0.000 < 0.05, it can be concluded that simultaneously there is a positive and significant influence of Work Discipline and Work Motivation on Employee Performance at PT Tridaya Dimensi Indonesia in South Jakarta.